COVID-19, Pre-Eclampsia, and Complement System - Agostinis, Chiara; Mangogna, Alessandro; Balduit, Andrea; Aghamajidi, Azin; Ricci, Giuseppe; Kishore, Uday; Bulla, Roberta (Frontiers in immunology, 2021)
COVID-19 is characterized by virus-induced injury leading to multi-organ failure, together with inflammatory reaction, endothelial cell (EC) injury, and prothrombotic coagulopathy with thrombotic events. Complement system (C) via its cross-talk with the contact and coagulation systems contributes significantly to the severity and pathological consequences due to SARS-CoV-2 infection. These immunopathological mechanisms overlap in COVID-19 and pre-eclampsia (PE). Thus, mothers contracting SARS-CoV-2 infection during pregnancy are more vulnerable to developing PE. SARS-CoV-2 infection of ECs, via its receptor ACE2 and co-receptor TMPRSS2, can provoke endothelial dysfunction and disruption of vascular integrity, causing hyperinflammation and hypercoagulability. This is aggravated by bradykinin increase due to inhibition of ACE2 activity by the virus. C is important for the progression of normal pregnancy, and its dysregulation can impact in the form of PE-like syndrome as a consequence of SARS-CoV-2 infection. Thus, there is also an overlap between treatment regimens of COVID-19 and PE. C inhibitors, especially those targeting C3 or MASP-2, are exciting options for treating COVID-19 and consequent PE. In this review, we examine the role of C, contact and coagulation systems as well as endothelial hyperactivation with respect to SARS-CoV-2 infection during pregnancy and likely development of PE.